Language Translator using Dictionary and APIs from English to Sindhi - Gangwani, Pinky; Ajani, Samir (International Journal of Computer Sciences and Engineering, 2025)
In India Language Translation systems have been developed for translation from English to Indian Languages and from regional languages to regional languages. These systems are also used for teaching machine translation to the students and researchers. Most of these systems are in the English to Hindi domain with exceptions of a Hindi to English and English to Kannada machine translation system. English is a SVO (subject-verb-object) language while Indian regional languages are SOV (subject-object-verb) and are relatively of free word-order. A survey of the machine translation systems that have been developed in media for translation from English to Indian languages and among Indian languages reveals that the machine translation software is used in field testing or is available as web translation service. We present an analysis regarding the performance of the state-of-art Phrase-based Language Translation (LT) on Indian Sindhi languages. We report baseline systems on Sindhi language pairs. The motivation of this study is to promote the development of SLT and linguistic resources for these language pairs, as the current state-of-the-art is quite bleak due to sparse data resources. The success of an SLT system is contingent on the availability of a large parallel corpus i.e. Dictionary. Such data is necessary to reliably estimate translation probabilities.